In Vitro Biofilm Formation on Titanium and Zirconia Implant Surfaces. Issue 3 (1st March 2017) - Roehling, Stefan; Astasov‐Frauenhoffer, Monika; Hauser‐Gerspach, Irmgard; Braissant, Olivier; Woelfler, Henriette; Waltimo, Tuomas; Kniha, Heinz; Gahlert, Michael
Abstract : Background: It has been hypothesized that zirconia might have a reduced bacterial adhesion compared with titanium; however, results from experimental studies are rather controversial. The aim of the present study is to compare biofilm formation on zirconia and titanium implant surfaces using an in vitro three‐species biofilm and human plaque samples. Methods: Experimental disks made of titanium (Ti) or zirconia (ZrO2 ) with a machined (M) or a sandblasted (SLA) and acid‐etched (ZLA) surface topography were produced. An in vitro three‐species biofilm or human plaque samples were applied for bacterial adhesion to each type of disk, which after 72 hours of incubation was assessed using an anaerobic flow chamber model. Results: Zirconia showed a statistically significant reduction in three‐species biofilm thickness compared with titanium (ZrO2 ‐M: 8.41 μm; ZrO2 ‐ZLA: 17.47 μm; Ti‐M: 13.12 μm; Ti‐SLA: 21.97 μm); however, no differences were found regarding three‐species‐biofilm mass and metabolism. Human plaque analysis showed optical density values of 0.06 and 0.08 for ZrO2 ‐M and ZrO2 ‐ZLA, and values of 0.1 and 0.13 for Ti‐M and Ti‐SLA, respectively; indicating a statistically significant reduction in human biofilm mass on zirconia compared with titanium. Additionally, zirconia revealed a statistically significant reduction in human plaque thickness (ZrO2 ‐M: 9.04 μm; ZrO2 ‐ZLA: 13.83 μm; Ti‐M: 13.42 μm; Ti‐SLA: 21.3 μm) but a similar human plaque metabolism compared with titanium. Conclusion: Zirconia implant surfaces showed a statistically significant reduction in human plaque biofilm formation after 72 hours of incubation in an experimental anaerobic flow chamber model compared with titanium implant surfaces.